Analisis Sikap Mahasiswa Terhadap Hasil Belajar Materi Kuliah Statistik Probabilitas - Saftari, Maya; marna, Marna; sariman, sariman (Department of Mathematics Education , University of Jember, 2021)
Research to describe whether the results of the assessment in the affective domain affect student learning outcomes on the subject matter of Probability Statistics. One of the assessments of the affective domain is attitude assessment. The research approach is a quantitative research with an analysis of the research subject of 100 students who have taught the Probability Statistics course. This research was conducted using an instrument in the form of an attitude scale questionnaire based on a Likert scale consisting of 22 questions with answers to questions including: Always (SL) points 5, Often (SR) points 4, Sometimes (K) points 3, Rarely (JR) point 2, and Never (TP) point 1 which is based on the attitude scale instrument grid in the form of a checklist. The indicators measured on the attitude scale are interest, curiosity, attention in learning and self-confidence. The method of analysis in the form of a correlation survey is to see the influence of the affective domain on student learning outcomes. From the results of the research, it is known that the effect of learning outcomes based on student attitudes is the most prominent due to the interest and confidence of students who are in charge of the Probability Statistics course. For curiosity and attention in learning do not have a direct effect on learning outcomes.